Indigenous Community Marriage Communication as a Social Adhesive Media - Dortje L. Y Lopulalan (MultiTech Publisher, 2023)
People could play a part in creating folks' beliefs about a way of life-based on a system of values, norms, and local wisdom that is adhered to and believed in by using symbolic aspects of traditional values. This manner of thinking as well as setting further contributes to or rather performs an important role in the traditional marital system throughout crystallizing kinship relationships among another the last, and it has the potential to become a medium for initiating social glue that constructs unique social relations between individuals and groups that differ in identity as well as group. This qualitative descriptive research utilized a phenomenological method (a phenomenological approach is a qualitative research tradition rooted in philosophy and psychology that focuses on personal human experiences (sociology).